PENINGKATAN KUALITAS GURU MELALUI PELATIHAN PENGEMBANGAN LEARNING MANAGEMENT SYSTEM BERBASIS DARING PADA MGMP MATEMATIKA KABUPATEN BOGOR - Tri Murdiyanto Murdiyanto; Makmuri; mulyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract This Community Service (P2M) activity aims to improve the learning quality of junior high school mathematics teachers in Bogor district in carrying out online learning. The collaboration partner in this service activity is Mathematics MGMP in Bogor district. During the COVID-19 pandemic, learning in schools is carried out online where the ability of teachers to design, manage, and evaluate learning outcomes is required. The learning plan at each meeting is arranged in a pattern that includes web meetings/video conferences, discussion forums, website links and learning video links, as well as learning evaluations. Activities carried out: renting hosting for 3 years and installing Moodle LMS which is used as a place to design lessons, technical explanations related to learning designs that must be made in the LMS, participants are guided to practice making lesson plans, formed 6 groups for workshops to complete junior high school mathematics learning designs that covering 6 semesters, monitoring is carried out directly from the resulting LMS and guidance is carried out through the whatsapp group. The result of community service is that teachers are able to make learning designs using learning technology, especially the Learning Management System (LMS). The product from this training / workshop can be used by teachers during online learning. and even in normal learning, this product can still be used as blended learning. The conclusion of the results of community service is that junior high school mathematics teachers are able to use the Learning Management System (LMS) in designing and managing learning, and also in evaluating learning outcomes. Abstrak Kegiatan Pengabdian Kepada Masyakat (P2M) ini bertujuan untuk meningkatkan kualitas pembelajaran guru matematika SMP di kabupaten Bogor dalam melaksanakan pembelajaran secara daring. Mitra kerjasama pada kegiatan pengabdian ini adalah MGMP Matematika kabupaten Bogor. Pada masa pandemi covid-19 pembelajaran di sekolah dilakukan secara daring dimana diperlukan kemampuan guru untuk merancang, mengelola, dan mengevaluasi hasil pembelajaran. Rancangan pembelajaran pada setiap pertemuan disusun dengan pola yang memuat web meeting/video converence, forum diskusi, link website dan link video pembelajaran, serta evaluasi pembelajaran. Kegiatan yang dilaksanakan: menyewa hosting selama 3 tahun dan instalasi LMS moodle yang digunakan sebagai tempat merancang pembelajaran, penjelasan teknis berkaitan dengan rancangan pembelajaran yang harus dibuat dalam LMS, peserta dipandu mempraktekkan pembuatan rancangan pembelajaran, dibentuk 6 kelompok untuk workshop menyelesaikan rancangan pembelajaran matematika SMP yang meliputi 6 semester, monitoring dilaksanakan langsung dari LMS yang dihasilkan dan dilakukan bimbingan melalui whatsapp group. Hasil pengabdian kepada masyarakat yaitu guru-guru mampu membuat rancangan pembelajaran dengan menggunakan teknologi pembelajaran, khususnya Learning Management System (LMS). Produk hasil pelatihan/workshop ini dapat digunakan guru selama pembelajaran daring. dan pada pembelajaran normal pun produk ini tetap dapat digunakan menjadi pembelajaran blended learning. Kesimpulan hasil pengabdian kepada masyarakat yaitu bahwa guru-guru matematika SMP mampu menggunakan Learning Management System (LMS) dalam merancang dan mengelola pembelajaran, dan juga di dalam mengevaluasi hasil pembelajaran.